2011
DOI: 10.1021/jz200993d
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Tuned Initial Excited-State Structural Dynamics of DNA Nucleobases from UV Resonance Raman Spectroscopy: 5-Deuterouracil

Abstract: 5-Deuterouracil (5-d-U) is an analogue of uracil (RNA) and thymine (DNA), which differ only in the mass of their 5-substituent. Previous work has shown that the initial excited-state structural dynamics primarily lie along C5C6 bond lengthening in thymine, while these dynamics primarily lie along C5 and C6 pyramidalization in uracil. To test whether the 5-substituent mass determines these dynamics, the resonance Raman spectra of 5-d-U, with a 5-substituent mass intermediate between uracil and thymine, is meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 15 publications
7
37
0
Order By: Relevance
“…However, an unexpectedly upward trend is observed in the 1235 cm −1 mode, which causes a poorer fit to the experimental RREP of this normal mode. The shape of this resonance Raman cross-section excitation profile may be due to resonance with [21], γ(C2N3) [11], ring def 6 [10], γ(C4O10) [9], γ(C5H11) [8] the higher electronic transition. Further experimentation is necessary to characterize the UV resonance Raman excitation profiles in the 1235 cm −1 mode of both molecules at higher energies.…”
Section: ■ Theorymentioning
confidence: 96%
See 2 more Smart Citations
“…However, an unexpectedly upward trend is observed in the 1235 cm −1 mode, which causes a poorer fit to the experimental RREP of this normal mode. The shape of this resonance Raman cross-section excitation profile may be due to resonance with [21], γ(C2N3) [11], ring def 6 [10], γ(C4O10) [9], γ(C5H11) [8] the higher electronic transition. Further experimentation is necessary to characterize the UV resonance Raman excitation profiles in the 1235 cm −1 mode of both molecules at higher energies.…”
Section: ■ Theorymentioning
confidence: 96%
“…The general implementation of these equations for absorption and resonance Raman spectroscopy have been described in detail previously. [4][5][6][7][8][9][10][11][12][13][14]16,17 The vibrational mode assignments described in Tables 1 and 2 were obtained by DFT computation at the B3LYP/6-311G(d,p) level of theory, with the default gradients implemented in the Gaussian09 18 package performed on the initial planar C s structures of uracil and 6-MeU in the diketo tautomer form. The isotope effect was calculated for 6-d-U from the uracil frequencies, which are not scaled.…”
Section: ■ Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used for converting the resonance Raman intensities into differential cross sections have been described previously . The experimental resonance Raman differential cross sections of sulfate used for the calculations were 3.30×10 −12 , 2.87×10 −12 , 2.42×10 −12 , and 2.05×10 −12 Å 2 molecule −1 sr −1 at λ =250, 257, 266, and 275 nm, respectively …”
Section: Methodsmentioning
confidence: 99%
“…The initial excited‐state structural dynamics of nucleobases with short‐lived excited‐states can be obtained by using resonance Raman intensities, absorption spectra, and a self‐consistent time‐dependent wavepacket formalism. Such an analysis has been performed on numerous uracil derivatives in an attempt to elucidate photochemical mechanisms in DNA components. Previous elucidation of the initial excited‐state structural dynamics of C5‐and C6‐methylated uracil derivatives have shown that methyl substitution increases the initial excited‐state structural dynamics along the C5−C6 bond‐lengthening coordinate .…”
Section: Introductionmentioning
confidence: 99%